2008
DOI: 10.1128/aac.00585-07
|View full text |Cite
|
Sign up to set email alerts
|

Human Pre-Elafin Inhibits a Pseudomonas aeruginosa -Secreted Peptidase and Prevents Its Proliferation in Complex Media

Abstract: Pseudomonas aeruginosa is a life-threatening opportunist human pathogen frequently associated with lung inflammatory diseases, namely, cystic fibrosis. Like other species, this gram-negative bacteria is increasingly drug resistant. During the past decade, intensive research efforts have been focused on the identification of natural innate defense molecules with broad antimicrobial activities, collectively known as antimicrobial peptides. Human pre-elafin, best characterized as a potent inhibitor of neutrophil … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 38 publications
0
28
0
Order By: Relevance
“…[33] Also, aerosol treatment with elastase inhibitor enhanced bacterial clearance in an in vitro model of chronic P. aeruginosa lung infection. [32] Clinical studies will be necessary to extend these observations to humans, and to determine whether protease inhibition can inhibit progression of CF lung disease in CF patients. [20,34] …”
Section: Antimicrobial Peptidesmentioning
confidence: 97%
See 1 more Smart Citation
“…[33] Also, aerosol treatment with elastase inhibitor enhanced bacterial clearance in an in vitro model of chronic P. aeruginosa lung infection. [32] Clinical studies will be necessary to extend these observations to humans, and to determine whether protease inhibition can inhibit progression of CF lung disease in CF patients. [20,34] …”
Section: Antimicrobial Peptidesmentioning
confidence: 97%
“…Elafin is cleaved by its cognate enzyme neutrophil elastase, which is present in excessive concentrations in CF sputum, especially when the lung is colonized by P. aeruginosa. [31,32] Recombinant human elastase inhibitor was tested in a rat model of acute pulmonary damage, where it prevented injury caused by instillation of human secretions of CF sputum. [33] Also, aerosol treatment with elastase inhibitor enhanced bacterial clearance in an in vitro model of chronic P. aeruginosa lung infection.…”
Section: Antimicrobial Peptidesmentioning
confidence: 99%
“…The observed resistance of elafin to proteolysis mediated by Pseudomonas serine protease(s) suggests that it is not as sensitive as SLPI and AAT, or may be explained by the capacity of elafin to inhibit serine protease(s) secreted by the pathogenic microorganism. Indeed, a recent study suggests that elafin inhibits growth of P. aeruginosa in complex media via the inhibition of a serine protease produced by the pathogen, presumably the arginyl peptidase protease IV (Bellemare et al , 2008). Identification of the Pseudomonas metalloprotease(s) involved in the cleavage and inactivation of elafin was carried out using purified Pseudomonas metalloproteases: pseudolysin, staphylolysin (LasA) and aeruginolysin ( Pseudomonas alkaline protease, serralysin).…”
Section: Discussionmentioning
confidence: 99%
“…Apart from its well known inhibitory properties, pre-elafin has been found to have broad antimicrobial properties in vitro and in vivo (14,(46)(47)(48). Although the biochemical mechanism responsible for the antimicrobial activities has not yet been elucidated, it is well known that the antimicrobial activities of pre-elafin are independent of their antiproteinase function (47)(48)(49).…”
Section: Discussionmentioning
confidence: 99%
“…Although the biochemical mechanism responsible for the antimicrobial activities has not yet been elucidated, it is well known that the antimicrobial activities of pre-elafin are independent of their antiproteinase function (47)(48)(49). Recent studies have demonstrated that the N terminus of pre-elafin, responsible for most of the antimicrobial activity of the protein, adopts an a-helical conformation in the presence of a membrane mimetic, which is typical of many antimicrobial peptides (49).…”
Section: Discussionmentioning
confidence: 99%